Refugees and rural development: Chances from migration and challenges of integration - Kim Pollermann (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The current immigration of refugees leads to a discussion about links between rural development and migration. Some rural regions in Germany formulate the hope that they can benefit from refugee immigration. In these areas, the impacts of aging and population decline with labour and skills shortages are often more relevant than in larger cities. So the questions are: What are the chances from refugee immigration? For which kind of rural areas are these opportunities realistic? And which framework conditions and governance arrangements for integration are conducive to using these opportunities? With regard to the attractiveness of various rural areas in Germany for immigration and their integration abilities, the conditions are quite different while in Eastern Germany the possibilities are lower. Multi-level-integration governance is required to make the best use of the chances. To shape suitable framework conditions for integration there is a need of a region specific, integrated view on the different factors of integration. – – Einige ländliche Regionen formulieren Hoffnungen, dass diese von der Immigration von Geflüchteten profitieren können. In diesen Regionen sind die Wirkungen der Alterung und des Rückgangs der Bevölkerung (einhergehend mit dem Mangel insbesondere von Fachkräften) oft bedeutsamer als in größeren Städten. Somit stellen sich die Fragen: Was sind Chancen der Immigration? Für welche der ländlichen Räume sind solche Optionen realistisch? Und welche Rahmenbedingungen und Governance Arrangements zur Integration unterstützen die Nutzung dieser Optionen?
Conference: IAMO Forum 2016, Rural Labor in Transition: Structural Change, Migration and Governance Halle/Saale, Germany (22.6.2016)
Keywords: R; R58; 330; Rural development; Integration; Refugees; Migration; Germany